2007
DOI: 10.1246/cl.2007.1274
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Base Additives on the Selective Hydrogenolysis of Glycerol over Ru/TiO2 Catalyst

Abstract: Under mild reaction conditions (170 °C, 3 MPa), glycerol is hydrogenolyzed to 1,2-propanediol with very high selectivity at high conversion using Ru/TiO2 as catalyst in basic aqueous solution. The base aids the initial dehydrogenation of glycerol to glyceraldehyde and promotes the dehydration of glyceraldehyde to 2-hydroxyacrolein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(52 citation statements)
references
References 15 publications
4
38
0
Order By: Relevance
“…The presence of NaOH resulted in a significant increase in the glycerol conversion from 5.2% to 22%, suggesting that the base can serve as a co-catalyst in the hydrogenolysis of glycerol. This agrees well with results obtained in literature by different catalysts under basic conditions, as an increase in the catalyst activity was expected in the [6,30]. In addition, a remarkable change in the selectivity of 1,2-PD, H-AC, AC, and EG was observed.…”
Section: Effect Of Stirring Speedsupporting
confidence: 92%
“…The presence of NaOH resulted in a significant increase in the glycerol conversion from 5.2% to 22%, suggesting that the base can serve as a co-catalyst in the hydrogenolysis of glycerol. This agrees well with results obtained in literature by different catalysts under basic conditions, as an increase in the catalyst activity was expected in the [6,30]. In addition, a remarkable change in the selectivity of 1,2-PD, H-AC, AC, and EG was observed.…”
Section: Effect Of Stirring Speedsupporting
confidence: 92%
“…In fact, there may be a competition of cleavage between the C-O bonds and C-C bonds. Many reports proposed and confirmed that glycerol hydrogenolysis was conducted by dehydration/hydrogenation mechanism [33][34][35] as shown in Fig. 11.…”
Section: Catalytic Performance Of Ni-co Catalysts and Ce Promoted Ni mentioning
confidence: 81%
“…Catalyst systems involving various compositions of copper chromite as well as supported noble metals have been reported for the conversion of glycerol to 1,2-PDO in presence of a solvent under high pressure and temperature conditions [9,[16][17][18]. Among noble metals, Pd, Pt, Ru and Rh have been used on various supports for the hydrogenolysis of glycerol [19,20]. Castle and Gomez first described glycerol hydrogenolysis using copper and zinc catalyst as well as sulfided Ru catalyst under very high pressure and temperature conditions (15 MPa; 513-545 K) with 75-85% selectivity to 1,2-PDO while [25% were cracked products such as EG, ethanol, methanol and lactic acid [21,22].…”
Section: Introductionmentioning
confidence: 99%